2015
DOI: 10.1186/s12864-015-1389-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in Rana pirica tadpoles following exposure to a predation threat

Abstract: BackgroundRana pirica tadpoles show morphological changes in response to a predation threat: larvae of the dragonfly Aeshna nigroflava induce heightened tail depth, whereas larval salamander Hynobius retardatus induce a bulgy morphology with heightened tail depth. Although both predators induce similar tail morphologies, it is possible that there are functional differences between these tail morphs.ResultsHere, we performed a discriminant microarray analysis using Xenopus laevis genome arrays to compare tail t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Wildlife trade is responsible for the introduction of numerous species into new environments globally (Souviron-Priego et al, 2018), including amphibians. Invasive species generally have negative impacts on local species through predation, competition (Mori et al, 2015;Sarashina and Yoshida, 2015) and other ecological interactions (Buckley and Catford, 2016), including carrying non-native pathogens (Bezerra-Santos et al, 2021). This is also the case in Ranidae species, such as Pelophylax ridibundus in the UK (Zeisset and Beebee, 2003), and several species in the focal area of this study, including Rana huanrenensis that has been introduced to offshore islands in the Republic of Korea (Bae et al, 2022).…”
Section: Introduction 1species Introductionmentioning
confidence: 70%
“…Wildlife trade is responsible for the introduction of numerous species into new environments globally (Souviron-Priego et al, 2018), including amphibians. Invasive species generally have negative impacts on local species through predation, competition (Mori et al, 2015;Sarashina and Yoshida, 2015) and other ecological interactions (Buckley and Catford, 2016), including carrying non-native pathogens (Bezerra-Santos et al, 2021). This is also the case in Ranidae species, such as Pelophylax ridibundus in the UK (Zeisset and Beebee, 2003), and several species in the focal area of this study, including Rana huanrenensis that has been introduced to offshore islands in the Republic of Korea (Bae et al, 2022).…”
Section: Introduction 1species Introductionmentioning
confidence: 70%
“…Several animal species with genetic alterations of the DMD gene also display strong fear-related behavioral disturbances and enhanced stress reactivity ( Frésard et al, 2012 ; Nonneman et al, 2012 ; Mori et al, 2015 ). Moreover, several studies and reports of parents' rating have revealed internalizing problems, including anxiety in Duchenne and Becker muscular dystrophies, which likely contribute to and/or enhance maladaptive social behaviors and neuropsychiatric disturbances ( Poysky and Behavior in DMD Study Group, 2007 ; Young et al, 2008 ; Snow et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We collected Rana pilica eggs from ponds in the Hokkaido Prefecture and hatched them in our laboratory as described. 11 Tadpoles were then bred for 10 days and harvested using cryopreservation as described. 12 Briefly, tadpoles without tails were freeze embedded in blocks with 4%…”
Section: Preparation Of Tissue Sectionsmentioning
confidence: 99%
“…We investigated metabolite dynamics in the tadpoles under stress predation 11,14 and metamorphosis. We previously attempted to determine the distribution of thyroid hormone metabolites on Film sections, 8 but small amounts of metabolites were difficult to localize.…”
Section: Application Of Maldi-ms Imaging To Tadpolesmentioning
confidence: 99%